Análisis del procedimiento administrativo de atención de reclamos para la satisfacción del usuario de Osirnergmin Iquitos, 2018 - Ramírez Mendoza, Ruth Eliana (2019)
The present investigation is entitled “Analysis of the administrative procedure of attention of claims for the satisfaction of the user of Osinergmin Iquitos, 2018” was developed, in the city of Iquitos, Province of Maynas, department of Loreto, which had as main objective to analyze the administrative procedure of attention of complaints for the satisfaction of the user of Osinergmin, Iquitos 2018, the methodology has been developed with the type of study applied, the design of the research is non-experimental, had as sample 64 users of Osinergmin Iquitos, whose instrument was the survey. Coming to conclude in this way that the administrative procedure of attention of claims of the Osinergmin institution is regular in a 53%, the level of satisfaction of the user with respect to the concessionary company providing electric distribution service Electro Oriente SA (hereinafter the concessionaire ) is 59% average and finally a statistical evidence of Pearson's correlation of 0.850 could be obtained, between the variables Administrative procedure of attention of complaints and user satisfaction where it is verified that if there is a considerable positive correlation thus allowing the hypothesis testing.